2010
DOI: 10.1167/iovs.10-5753
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cellular Bouton Structure Activated by ATP in the Vascular Wall of Porcine Retinal Arterioles

Abstract: The vasodilating effect of purines in porcine retinal tissue involves ATP-dependent calcium activity in a layer of cellular boutons located external to the vascular smooth muscle cells and internal to the perivascular glial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…The present study confirms results from previous studies that PGE 2 can induce concentration dependent relaxation and PGF 2 a a less pronounced contraction of porcine retinal arterioles in vitro (Holmgaard and Bek, 2010;Misfeldt et al, 2010a;Yu et al, 2001). The protocol used to study the effects of the two prostaglandins was designed to elicit opposite tone responses which required that the relaxing effect of PGE 2 was studied after pre-contraction (Holmgaard and Bek, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present study confirms results from previous studies that PGE 2 can induce concentration dependent relaxation and PGF 2 a a less pronounced contraction of porcine retinal arterioles in vitro (Holmgaard and Bek, 2010;Misfeldt et al, 2010a;Yu et al, 2001). The protocol used to study the effects of the two prostaglandins was designed to elicit opposite tone responses which required that the relaxing effect of PGE 2 was studied after pre-contraction (Holmgaard and Bek, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…The PVCs located outside the retinal arteriolar smooth muscle cells have previously been shown to have increased Ca 2þ activity simultaneously with relaxation induced by both ATP and PGE 2 (Misfeldt et al, 2013(Misfeldt et al, , 2010a, but in the present study a similar increase in Ca 2þ activity was observed in these cells during contraction induced by both the prostaglandin analogue U46619, PGF 2a and the unspecific depolarizing agent KPSS. An involvement of the PVCs in the modulation of vascular tone might be expected to depend on recruitment through different Ca 2þ channels during contraction and relaxation.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Thus, it has been shown that ATP stimulates intracellular calcium activity in perivascular cells [34,35], and intracellular calcium levels are elevated in retinal cell cultures exposed to hyperglycaemia [8]. Furthermore, retinal blood flow is affected by activation of P 2 receptors in alloxan-induced diabetes in rabbits [36,37], and a recent study has shown that ATP relaxation of porcine retinal arterioles exposed to hypercholesterolaemia in vivo is modified by both hepatic low-density lipoprotein receptor deficiency and diabetes mellitus [38].…”
Section: Discussionmentioning
confidence: 99%